The Construction of Health Communication: International and Multidisciplinary Perspectives (The Journal of Medicine, Humanity and Media, 2026)
Health communication stands at a transformative juncture, shaped by rapid technological evolution, persistent global health disparities, and a deepening recognition that effective health promotion demands more than information dissemination. This issue brings together fourteen cutting-edge contributions, including a review of the work of twelve leading scholars and three independent research articles. This collection traces a coherent arc from theoretical innovation to pragmatic intervention, illuminating how communication can bridge the gaps between policy and practice, technology and humanity, global frameworks and local realities. Representing diverse geographical and intellectual traditions—from Singapore to South Africa, from the Netherlands to New Zealand—these contributions underscore the field’s maturation into a truly global, multidisciplinary enterprise.